2018
DOI: 10.3847/2041-8213/aae8e4
|View full text |Cite
|
Sign up to set email alerts
|

SOFIA FIFI-LS Observations of Sgr B1: Ionization Structure and Sources of Excitation

Abstract: The current paradigm of Galactic Center (GC) gas motions and star formation envisions sequential star formation in streams of gas as they pass near the supermassive black hole, Sgr A*. This is based on the relative positions of dense molecular clouds, the very young star-forming region Sgr B2, the much older region Sgr C, and the several Myr old Arches and Quintuplet Clusters. Because Sgr B1 is found with Sgr B2 in a common envelope of molecular gas and far-infrared emission, the two sources are thought to be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…This idea is supported by simulations of the gas (Dale et al 2019) and observations of the evolution of gas properties along portions of the stream (Krieger et al 2017). However, this model is likely not sufficient to describe all of the star formation observed in the CMZ (Kendrew et al 2013;Simpson et al 2018); Jeffreson et al (2018) estimate that 20% of CMZ clouds may be tidally forced into star formation.…”
Section: Introductionmentioning
confidence: 96%
“…This idea is supported by simulations of the gas (Dale et al 2019) and observations of the evolution of gas properties along portions of the stream (Krieger et al 2017). However, this model is likely not sufficient to describe all of the star formation observed in the CMZ (Kendrew et al 2013;Simpson et al 2018); Jeffreson et al (2018) estimate that 20% of CMZ clouds may be tidally forced into star formation.…”
Section: Introductionmentioning
confidence: 96%
“…There is, however, a strong ridge of warm dust emission immediately adjacent to one of the Wolf-Rayet stars found in Mauerhan et al (2010) that does not have a strong radio counterpart and might be evidence of the impact of a orbiting massive star not formed in situ. Simpson et al (2018) suggested, based on maps of the [O III] 52 and 88 µm lines in Sgr B1 with FIFI-LS, that the region may not, in fact, be forming stars as we see in Sgr B2, but rather the observed emission may be the result of passing massive stars, such as is seen in the regions surrounding the Arches and Quintuplet clusters.…”
Section: The Sgr B1 and Sgr B2 Complexesmentioning
confidence: 65%
“…In contrast, Sgr B1 is a more evolved star-forming region kinematically linked to Sgr B2, which contains a population of less extinct (embedded) H II regions (Mehringer et al 1992(Mehringer et al , 1993Lang et al 2010). There is, however, recent evidence to suggest that these H II regions are a result of evolved massive stars passing through the dense medium in Sgr B1, as opposed to young O/B-stars that have formed within the cloud (Simpson et al 2018).…”
Section: The Sgr B1 and Sgr B2 Complexesmentioning
confidence: 99%
“…However, the only two known Galactic center young clusters account for <10% of the expected young stellar mass 8 . Studying Sgr B1, a luminous Galactic center HII region 9 , we find evidence for the presence of several 𝟏𝟎 𝟓 𝑴 ⨀ of young stars, probably tracing one or several dissolved young clusters that formed ~10 Myr ago. This is a large step toward a better understanding of star formation at the Galactic center, such as the fate of young clusters, and the possibly different initial mass function in this region.…”
mentioning
confidence: 89%
“…Sagittarius (Sgr) B1 is a well-known HII region in the Galactic center 9 . Far-infrared observations suggests that it contains substantial amounts of young massive stars 9 .…”
mentioning
confidence: 99%